Über Wissenschaft reden. Studien zu Sprachgebrauch, Darstellung und Adressierung in der deutschsprachigen Wissenschaftsprosa um 1800 - Weidner, Daniel,Haas, Claude (De Gruyter, 2019)
The volume examines the relationship between scientific self-understanding and scientific language usage in the German-speaking world around 1800. It discusses the re-founding of the university, the fraught relationship with rhetorical tradition, the presentational impact of scientific speech, and the political implications for audiences of this discourse
10.1515/9783110676631
Keywords: Deutsch; Wissenschaftssprache; Sprachgebrauch; Vorlesung; Rede